(untitled) (Annals of the Institute of Biology, 2022)
Species Seseli tomentosum Vis. is an endemic and endangered species. It is an extremely poorly researched species in Bosnia and Herzegovina. The first recorded information about the appearance of this species in Bosnia and Herzegovina dates from 1967. This paper presents the chronology and spatial distribution of the species Seseli tomentosum Vis. in Bosnia and Herzegovina.